2005
DOI: 10.1038/oby.2005.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energy‐Reduced Diets High in Dairy Products and Fiber on Weight Loss in Obese Adults

Abstract: Objective: Studies suggest that high-dairy and high-fiber/ low-glycemic index diets may facilitate weight loss, but data are conflicting. The effects on weight loss and body fat of a high-dairy diet and a diet high in dairy and fiber and low in glycemic index were compared with a standard diet. Research Methods and Procedures: Ninety obese subjects were recruited into a randomized trial of three diets designed to provide a calorie deficit of 500 calories/d over a 48-week period. The study compared a moderate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
172
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(186 citation statements)
references
References 49 publications
(53 reference statements)
8
172
0
6
Order By: Relevance
“…The present results showed, in agreement with others (3,18) , that a calciumþD supplementation induced no statistically significant increase in fat mass loss in response to an energy restriction. On the other hand, and also in accordance with studies in low-calcium consumers (1,2) , women in the present study characterized by a calcium intake ,600 mg/d who received the calciumþD experienced a weight and fat loss more than four times that observed in their placebo counterparts who did not lose weight significantly despite their efforts to comply with the dietitian's nutritional guidelines.…”
Section: Discussionsupporting
confidence: 94%
“…The present results showed, in agreement with others (3,18) , that a calciumþD supplementation induced no statistically significant increase in fat mass loss in response to an energy restriction. On the other hand, and also in accordance with studies in low-calcium consumers (1,2) , women in the present study characterized by a calcium intake ,600 mg/d who received the calciumþD experienced a weight and fat loss more than four times that observed in their placebo counterparts who did not lose weight significantly despite their efforts to comply with the dietitian's nutritional guidelines.…”
Section: Discussionsupporting
confidence: 94%
“…Supplementation with a milk drink for 12 weeks in hypertensive adults had no significant impact on inflammatory marker levels like CRP and IL-6 (44) . Not only dairy consumption (40)(41)(42)(43) , but also supplementation with Ca and vitamin D (two major components of dairy products) for 3 years could not affect systemic inflammation (35) . However, in two recent clinical trials (45,46) , vitamin D supplementation markedly reduced the serum levels of CRP and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…50 Narrative reviews that considered the effect of increasing dairy intake along with energy restriction have reached conflicting findings. For instance, Dougkas et al 3 found five RCTs with energy restriction in their review, and reported that three studies showed no evidence, 33,43,44 whereas two studies 27,28 found significant effect of increasing dairy consumption along with weight loss diets on weight reduction. However, the search methodology used by Dougkas et al 3 seems to be incomplete because we found 11 studies that assessed the effect of dairy-rich weight loss diets on weight change.…”
Section: Discussionmentioning
confidence: 99%